Stress management among administrator and seniors teachers of private Islamic school - Hashim, Che Noraini; Kayode, Bakare Kazeem (The Journal of Global Business Management, 2010)
The school system is a green pasture for inexhaustible investigations for the purpose of enhancing academic achievement. This is particularly true, because factors and variables within the confines of educational activities appear also to be inexhaustible. One of such factor that attracted an investigation is 'occupational stress' as it affects school administrators and senior teachers. Therefore, this study, intends to investigate the underlying factors and structure of occupational stress facing Islamic school administrators and senior teachers in selected private Islamic schools in Klang Valley and how they manage stress within administrative and management function of these schools. The aspects that were investigated include—Administrative Responsibility, Workload, inadequate resources, work environment and lack of support from parent staff and coping methods. Instrument used in this study consisted of (38 item) questionnaire The questionnaire was adapted from the one developed by Chyuan1998: Occupational stress among school Administrators in Malaysia with special Reference to Temeloh District Pahang. One hundred and thirty (130) Malaysia administrators and senior teachers participated in the study. A principal component analysis (PCA) with varimax rotation yielded a 5-factor solution with satisfactory psychometric properties. The result also revealed that occupational stress is multidimensional measure consisting of five underlying factors. It is therefore concluded that even-though, stress management has a wider applicability, the scale may serve has a special relevance to stress management techniques, and may be of use in research and in stress management programmes. The result also revealed different stress management techniques use by the administrators and senior teachers.